2016
DOI: 10.1001/jamapsychiatry.2016.0383
|View full text |Cite
|
Sign up to set email alerts
|

Attention-Deficit/Hyperactivity Disorder Trajectories From Childhood to Young Adulthood

Abstract: The findings of this study do not support the assumption that adulthood ADHD is necessarily a continuation of childhood ADHD. Rather, they suggest the existence of 2 syndromes that have distinct developmental trajectories.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
253
1
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 283 publications
(289 citation statements)
references
References 22 publications
12
253
1
7
Order By: Relevance
“…In this UK longitudinal population‐based cohort, using updated SDQ cut‐points and excluding those with high scores at one time point during childhood, we find lower rates of genuine late‐onset ADHD (0.4%) than other population‐based studies (Moffitt et al., 2015, 2.7%; Agnew‐Blais et al., 2016, 5%; Caye et al., 2016, 7.9%). Indeed, in our sample, 75% (56 of 75 with full data) of those with apparent late‐onset ADHD symptoms were due to potential misclassification once we had taken into account subthreshold or elevated SDQ ADHD scores at least one point in childhood.…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…In this UK longitudinal population‐based cohort, using updated SDQ cut‐points and excluding those with high scores at one time point during childhood, we find lower rates of genuine late‐onset ADHD (0.4%) than other population‐based studies (Moffitt et al., 2015, 2.7%; Agnew‐Blais et al., 2016, 5%; Caye et al., 2016, 7.9%). Indeed, in our sample, 75% (56 of 75 with full data) of those with apparent late‐onset ADHD symptoms were due to potential misclassification once we had taken into account subthreshold or elevated SDQ ADHD scores at least one point in childhood.…”
Section: Discussionmentioning
confidence: 95%
“…(2015) found that their 3% prevalence of adult ADHD at age 38 years was 90% comprised of those without a history of childhood ADHD; Caye et al. (2016) found that 84.6% of their 18/19 year olds with ADHD did not have a history of childhood ADHD, and Agnew‐Blais et al. (2016) found that 67.5% of their 18 year olds with ADHD had not met criteria for ADHD at any assessment in childhood.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations